How Hands-On Pain Skills Intensive Trainings Complement ECHO Pain and Opioid Management Programs: A Program Evaluation with the Indian Health Service. Issue 9 (18th June 2020) - Katzman, Joanna G; Gygi, Kathleen; Swift, Robin; Comerci, George; Bhatt, Snehal; Daitz, Benson; Martin, Chamron; Fore, Chris
Abstract: Objective: To evaluate the impact of Pain Skills Intensive trainings (PSIs) as a complement to the Indian Health Service (IHS) and the Chronic Pain and Opioid Management TeleECHO Program (ECHO Pain) collaboration. Design: On-site PSIs conducted over two to three days were added to complement ECHO Pain at various IHS areas to enhance pain skills proficiency among primary care teams and to expand the reach of ECHO collaboration to ECHO nonparticipants. Setting: This evaluation focuses on two PSI trainings offered to IHS clinicians in Albuquerque, New Mexico, and Spokane, Washington, in 2017. Methods: The mixed-methods design comprises CME surveys and focus groups at the end of training and 12 to 18 months later. Quality of training and perceived competence were evaluated. Results: Thirty-eight participants attended the two PSI workshops. All provided CME survey results, and 28 consented to use of their postsession focus group results. Nine clinicians participated in the virtual follow-up focus groups. IHS clinicians rated the PSIs highly, noting their hands-on and interdisciplinary nature. They reported above-average confidence in their skills. Follow-up focus groups indicated they were pursuing expanded options for their patients, consulting other clinicians, serving as pain consultants to their peers, and changing prescribing practices clinic-wide. However, rurality significantly limits access to ancillary and complementary services for many. Clinicians reported the need for additional training in integrating behavioral health into their practice. Conclusions: Hands-on pain skills and information on medication-assisted treatment (MAT) are critical to the successful treatment of chronic pain and opioid use disorder. The PSIs provide clinicians with critical competencies in assessment and screening, pain management, and communication skills, complementing required IHS training and telementoring from ECHO Pain.